2017
DOI: 10.5114/ceji.2017.67321
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CD55, CD59, and CD35 on red blood cells of β-thalassaemia patients

Abstract: Aim of the studyβ-thalassaemia (β-Thal) is considered a severe, progressive haemolytic anaemia, which needs regular blood transfusions for life expectancy. Complement-mediated erythrocyte destruction can cause both intravascular and extravascular haemolysis. Complement regulatory proteins protect cells from such effects of the complement system. We aimed to perform quantitative analysis of membrane-bound complement regulators, CD55 (decay accelerating factor – DAF), CD35 (complement receptor type 1 – CR1), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…In line with our findings, Obaid et al, Kurtoǧllu et al, and Zahran et al found that expression of CD55 levels of β-thalassaemia patients were significantly decreased compared to healthy controls. On the other hand, they found there was no significant difference in the percentage of CD59 marker expression between β-thalassaemia patients and healthy controls [11] [18] [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with our findings, Obaid et al, Kurtoǧllu et al, and Zahran et al found that expression of CD55 levels of β-thalassaemia patients were significantly decreased compared to healthy controls. On the other hand, they found there was no significant difference in the percentage of CD59 marker expression between β-thalassaemia patients and healthy controls [11] [18] [19].…”
Section: Discussionmentioning
confidence: 99%
“…Decreases in complement regulatory protein (CrP) levels may predispose RBCs to destruction by complement activation. So, complement regulatory proteins are absolutely required to protect RBC from spontaneous complement damage that contributes to the development of anaemia [11].…”
Section: Introductionmentioning
confidence: 99%
“…Low CD55 levels in patients with β-TM indicate a role of the complement regulatory proteins, in the pathogenesis of haemolysis in this disorder, and therefore, a crucial role in the development of chronic complications described in these patients [50].…”
Section: β-Thalassemiamentioning
confidence: 93%
“…The pellets were suspended in sheath fluid. The optimal concentration for each antibody was determined by titration experiments 11Figure 1.Flow cytometric analyses of CD35, CD55 and CD59 on leukocytes:EDTA-treated blood was mixed with the following monoclonal antibodies; FITC-conjugated CD35, PE-conjugated CD55 and FITC-conjugated CD59; the samples were incubated for 20 mins in the dark at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The pellets were suspended in sheath fluid. The optimal concentration for each antibody was determined by titration experiments 11…”
Section: Methodsmentioning
confidence: 99%